Information technology project management - Schwalbe, Kathy (Course technology, 2002)
nformation Technology Project Management, Fifth Edition weaves theory and practice together, presenting a comprehensive, integrated view of the many concepts, skills, tools, and techniques involved in information technology project management. With the strong pedagogical features and straightforward approach that made previous editions popular, this revised edition continues to address the critical skills needed for success in the ever-expanding field of project management, which has grown in its impact on an increasing number of professions, most notably information technology. This text and its companion Web site will prove valuable information to anyone entering the corporate world, as government and industry leaders place an increasingly high value on effective project managers and project teams